Proteomic Analysis of Red Ginseng on Prolonging the Life Span of Male Drosophila melanogaster - Hou, Wei; Pei, Jin (Frontiers in Pharmacology, 2021)
Ginseng (Panax ginseng C. A. Mey.) is a traditional medicine that has been utilized for over 2000 years in Asia and shows varied pharmacological effects. Red ginseng (RG) is steamed and dried ginseng root and is considered to be more effective. Heating inactivates its catabolic enzymes and increases the activities of RG, which can improve the immune system, alleviate fatigue, and has anti-inflammatory effects and antioxidant activity. In addition, RG has a good anti-aging effect, but its mechanism is unclear. Senescence, a side-effect of normal developmental and metabolic processes, is a gradual decline in physiological integrity and function of the body. Senescence is usually associated with a variety of diseases, including neurodegenerative diseases and diabetes. Research on anti-aging and prolonging of life span has always been a focus topic. In this study, we investigated the molecular mechanism of RG that results in prolonged the life span for male Drosophila melanogaster. Isobaric tag for relative and absolute quantitation (iTRAQ) was used to identify protein changes in an old male D. melanogaster treated with RG. The differential proteins were verified by qRT-PCR and western blotting. The results showed that 12.5 mg/mL RG prolonged its life span significantly. iTRAQ results showed that, compared to the control group, 32 upregulated proteins and 62 downregulated proteins displayed significantly differential expression in the RG group. In this study, we explored the pathways that RG may participate in that extends the life span of D. melanogaster, and the results showed that the PI3K/AKT/FoxO pathway was involved. In addition, 4E-BP increased and participated in the regulation of life span.